The Influence of Earning Pershare (EPS), Return on Equity (Roe) and Debt to Equity Ratio (DER) on Stock Prices in Food and Beverage Manufacturing Companies Listed on The Indonesian Stock Exchange Period (2017 - 2022) - Nurul Nurul; Fanlia Prima Jaya (PT. Hanken Sukses Jaya, 2024)
The aim of this research is to find out and analyze which variables have the most dominant influence on share prices in food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2017 – 2022. The research method used is quantitative secondary data originating from financial reports listed on the Indonesia Stock Exchange. The population in this study was 30 manufacturing companies in the food and beverage sector and the sample in this study was 5 companies that had been selected using purposive sampling techniques and the data used was data used in financial reports for the period 2017 - 2022 consecutive years. The data analysis techniques used are frequency distribution and regression analysis. Linear analysis and multiple regression analysis were tested on SPSS 26..